«INVERTED LEARNING AS AN INNOVATIVE FORM OF EDUCATIONAL PROCESS ORGANIZATION» - Nazarenko, Lyudmila (Educological discourse, 2020)
The article highlights the need for positive changes in education through the use of innovative learning technologies. Analysis of scientific sources shows that this problem is urgent in the education system. Modern findings of equipping teachers with knowledge based on the innovations and child-centered approach are considered. The meaning and the content of flipped learning concept is specified; the own vision of the term is offered in the article. The principles of literary competence formation among high school students with the use of blended learning are substantiated and determined. The methodological aspects of the model application in a modern school are covered as well as its essence, features, advantages, possible difficulties and conditions which ensure the acquisition of literary education. The appropriateness of introducing such training in Ukrainian literature lessons is substantiated. The use of flipped learning at the Ukrainian literature lesson is demonstrated, due to which students acquire moral and ethical values. In the article there are covered methodological aspects of the Flipped Classroom, implementation possibilities of the competence approach in teaching of Ukrainian literature. The educational process is modeled in accordance with the modern requirements of student-oriented approach and task-based approach and Flipped classroom at the lesson of Ukrainian literature. The article proposes an algorithm based on the flipped learning for conducting the 11th grade Ukrainian literature lesson about the life and career of Valerian Pidmohylny. It is noted that the effective acquisition of knowledge occurs due to a combination of traditional and innovative learning, and it also depends on the student’s moral values and the staged use of technological learning. It is justified that the reading experience is based on the ability to analyze, interpret, compare, draw parallels, draw conclusions, use knowledge of literary theory in practice. It is primarily a combination of logical and sensory aspects, modern means of education, remote teaching and online learning, these components allow students to acquire competencies through projects, discussions and other activities. It is proved that the combination of traditional and innovative learning approaches including the virtual and real educational resources contributes to the transformation of literary knowledge into social and reading experience, prepares students for productive activities by turning them into active learners and changing teachers’ role from the main source of knowledge to facilitator.